6β-hydroxyipolamiide of Stachytarpheta jamaicensis Leaves - Yuliana Yuliana; Fithrotul Auwaliyah; Sri Fatmawati (IPTEK The Journal for Technology and Science, 2019)
Stachytarpheta jamaicensis is one species of Verbenaceae family that is used as a traditional medicine. 6β-hydroxyipolamiide is a natural occuring compound that was successfully isolated from S. jamaicensis leaves. The identification of compound was analyzed by using UV-Vis, Infra-Red (IR) spectrophotometry and Nuclear Magnetic Resonance (NMR) spectrometry. This is the first report that the compound has isolated from this plant.